Kajian filsafat kurikulum merdeka: Kurikulum merdeka dalam perspektif filsafat progresivisme dan humanisme - Chusniawati, Tasriatul (Maliki Interdisciplinary Journal, 2024)
The Merdeka Curriculum is a development of the 2013 Curriculum (K-13), which was originally introduced as an emergency curriculum during the Covid-19 pandemic, launched by the Indonesian government to provide freedom and free access to education for students, with an emphasis on the relevance of education to the needs of students and the development of interesting learning for educators. The research method used is library research, collecting various references from articles, books, and other scientific works. The Merdeka curriculum is designed based on the perspectives of progressivism and humanism, with a focus on developing students’ interests and talents and active learning. In the perspective of progressivism, this curriculum emphasizes the formation of independent and competent learners, capable of bringing positive changes in society through the application of knowledge in real life. The humanism perspective in this curriculum focuses on the comprehensive development of learners’ potential, including social, intellectual, emotional and moral aspects. In its implementation, the independent curriculum involves several important steps, such as designing a curriculum that is relevant to the times, using learner-centered learning methods, providing space for self-development outside the academic context, conducting evaluations that focus on learner progress, and creating an inclusive learning environment.